Localizing Islam in Europe: Turkish Islamic Communities in Germany and the Netherlands By Ahmet Yükleyen (New York: Syracuse University Press, 2012. 280 pages.) (American Journal of Islam and Society, 2013)
During April 2012, Salafi Muslims in Germany launched a Qur’an giveawayprogram to save non-Muslims from hell. Soon after, public debates emergedin the national media concerning broader Muslim transgressions in Europe.Especially the Turks, 3 million strong and two-thirds of Germany’s Muslimsaccording to the Federal Migration and Refugees Office, underwent furtherscrutiny. The August 17, 2012, issue of the popular news magazine Der Spiegelposited why Turkish Muslims escaped the backlash against Islamist radicalismthis time: Despite their proud Muslim identity, Turks living in Europe yearn tobe integrated and feel at home in Germany. Until recently, migration scholarsemphasized the incompatibility between Islam and western values, therebyportraying European Turks as another Muslim community that defied assimilation.Localizing Islam challenges this scholarship and explains why Turksfeel at home in Europe. It compares several Turkish Sunni organizations inGermany and the Netherlands, reinvents ways they interpret Islam, and arguesthat Islam’s inner diversity has endured within the European context ...